EVALUATION OF THE EFFICIENCY OF THE FINANCIAL PERFORMANCE OF THE ISLAMIC INSURANCE COMPANY IN JORDAN WITH A PROPOSED MODEL FOR THE ESTABLISHMENT OF AN ISLAMIC INSURANCE COMPANY IN IRAQ (American Journal of Business Management, Economics and Banking, 2023)
The increasing risks to which man is exposed and what he owns necessitates that he seeks to find ways to mitigate the negative effects of these risks. He resorted initially to saving and mutual support, but with the development of economic and social measures, a new idea was launched based on collective solidarity, and its main goal is to cooperate in covering damages that afflict a member of the group and guarantee his safety, and financial institutions have been established to practice insurance work, which requires the availability of two things: a legal relationship built between the insurer (the insurance company) and the insured (the insurance applicant) and technical and legal foundations that allow the establishment of such a relationship.With this development, the scope of The work of these companies and the methods of covering them led to the idea of establishing Islamic insurance companies that seek to attract shareholders who refuse to resort to traditional companies for fear of falling into legal problems.The research aimed to identify the concepts related to the insurance sector and the mechanisms of work of the insurance companies as well as to focus on the Islamic insurance sector and propose mechanisms to activate the activity of the Islamic insurance companies in Iraq by proposing a model that simulates the traditional companies. One of the important sectors, whether commercial or Islamic, is one of the urgent necessities that protect members of society from various dangers or reduce them as much as possible, and then recommended a set of recommendations, the most important of which are: Encouraging the establishment of traditional and Islamic Iraqi insurance companies working side by side, with the aim of increasing competition between these institutions from In order to compete in providing the best insurance services in a way that enhances the preservation of economic projects and protects them from various risks.